2022
DOI: 10.1371/journal.ppat.1010503
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine biosynthesis and eIF5A hypusination are modulated by the DNA tumor virus KSHV and promote KSHV viral infection

Abstract: Polyamines are critical metabolites involved in various cellular processes and often dysregulated in cancers. Kaposi’s sarcoma-associated Herpesvirus (KSHV), a defined human oncogenic virus, leads to profound alterations of host metabolic landscape to favor development of KSHV-associated malignancies. In our studies, we identified that polyamine biosynthesis and eIF5A hypusination are dynamically regulated by KSHV infection through modulation of key enzymes (ODC1 and DHPS) of these pathways. During KSHV latenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…In this study, we have shown that METTL16 mediates KSHV life cycle by regulating the splicing of MAT2A transcript and the intracellular SAM level. SAM is linked to multiple downstream pathways including polyamine synthesis, methylation of protein, DNA and RNA, and glutathione synthesis and ROS level [46,47], which have been linked to KSHV lytic replication [21,[32][33][34][35][36][37][38]. We have found that METTL16 or MAT2A knockdown reduces intracellular SAM and SAH levels leading to a lower GSH level and a higher ROS level, and hence increased KSHV lytic replication.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this study, we have shown that METTL16 mediates KSHV life cycle by regulating the splicing of MAT2A transcript and the intracellular SAM level. SAM is linked to multiple downstream pathways including polyamine synthesis, methylation of protein, DNA and RNA, and glutathione synthesis and ROS level [46,47], which have been linked to KSHV lytic replication [21,[32][33][34][35][36][37][38]. We have found that METTL16 or MAT2A knockdown reduces intracellular SAM and SAH levels leading to a lower GSH level and a higher ROS level, and hence increased KSHV lytic replication.…”
Section: Discussionmentioning
confidence: 81%
“…4A). Since numerous downstream pathways of SAM including transamination (polyamine synthesis), transmethylation (methylation of protein, DNA and RNA) and transsulfuration (glutathione synthesis) have been implicated in KSHV lytic replication [21,[32][33][34][35][36][37][38], we further examined the role of SAM in the KSHV lytic replication. SAM treatment reduced the numbers of GFP-positive cells in a concentration-dependent manner in NaB-induced cells (Fig.…”
Section: Mat2a Suppresses Kshv Lytic Replication and Mediates Mettl16...mentioning
confidence: 99%
“…It has previously been shown that eIF5A plays an important role in the replication of HIV ( Ruhl et al., 1993 ; Bevec et al., 1996 ; Andrus et al., 1998 ) as well as of ebola virus (EBOV) and marburg virus ( Olsen et al., 2016 ), and in the propagation of KSHV ( Fiches et al., 2022 ). Inhibition of hypusination has been proposed to suppress HIV gene expression at the level of transcription initiation ( Hoque et al., 2009 ) and blocking hypusination has been suggested to limit the effective translation of mRNA transcribed by the EBOV polymerase ( Olsen et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, metabolic analysis on three-dimensional cell cultures showed that KSHV infection enhanced nonessential amino acid and in particular proline and the associated polyamine metabolism [ 300 ]. Hypusine, a polyamine-derived amino acid, was shown to enhance LANA expression via hypusination of the eukaryotic initiation factor 5 A (eIF5A) [ 301 , 302 ]. Moreover, inhibition of polyamine biosynthesis or eIF5A hypusination decreased LANA expression, reduced viral episomal maintenance, and suppressed viral infection [ 301 , 302 ].…”
Section: Metabolic Reprogramming In Oncovirusesmentioning
confidence: 99%
“…Hypusine, a polyamine-derived amino acid, was shown to enhance LANA expression via hypusination of the eukaryotic initiation factor 5 A (eIF5A) [ 301 , 302 ]. Moreover, inhibition of polyamine biosynthesis or eIF5A hypusination decreased LANA expression, reduced viral episomal maintenance, and suppressed viral infection [ 301 , 302 ].…”
Section: Metabolic Reprogramming In Oncovirusesmentioning
confidence: 99%